PENGGUNAAN DIORAMA SEBAGAI SARANA INTERAKTIF DALAM PEMBELAJARAN IPAS UNTUK KELAS 5 SEKOLAH DASAR - Gigih Adilla Ayuningtyas; Elly Sukmanasa; Muhtar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore the use of dioramas as interactive tools in teaching Integrated Science and Social Studies (IPAS) for Grade 5. The research seeks to understand how dioramas are implemented in the learning context and their impact on students' learning experiences. Data were collected through interviews, classroom observations, and analysis of the use of dioramas with 29 students at SDN Panaragan 1. The findings indicate that dioramas enhance student engagement and facilitate a deeper understanding of IPAS concepts through a more visual and interactive approach. Dioramas help students develop critical and creative thinking skills and deepen their comprehension of the subject matter. The results provide insights into how dioramas can be more effectively integrated into IPAS.